2014
DOI: 10.1080/11250003.2014.920927
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size and shape dimorphism in the Wushan salamander,Liua shihi(Liu, 1950) (Urodela: Hynobiidae)

Abstract: Sexual dimorphism in size or shape is widespread in the animal world. Many studies have explored this topic, but few have focused on Asian salamanders. In this study, we analyzed morphometric data of the Wushan salamander Liua shihi, an endemic Chinese salamander, to examine sexual dimorphism in size and shape. We evaluated data sets that included 17 morphometric characteristics of 61 females and 55 males using univariate and multivariate methods. Results show that sexual dimorphism in this species includes no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…In cetaceans, sexual dimorphism often affects flipper length 14 , 20 , width 21 , or phalangeal count 22 . Similar sexual dimorphism in limb length is known in semiaquatic tetrapods such as some salamanders that engage in amplexus under water during copulation 23 , 24 , and has also been suggested for several pachypleurosaurs, such as Dactylosaurus , Keichousaurus , Neusticosaurus , and Serpianosaurus from the Triassic 5 , 25 – 27 . Not all cetaceans exhibit sexual dimorphism in flipper length 28 but we did not find any case where females had longer flippers than males for a given body size.…”
Section: Sexual Dimorphism In Extant Aquatic Tetrapodssupporting
confidence: 63%
“…In cetaceans, sexual dimorphism often affects flipper length 14 , 20 , width 21 , or phalangeal count 22 . Similar sexual dimorphism in limb length is known in semiaquatic tetrapods such as some salamanders that engage in amplexus under water during copulation 23 , 24 , and has also been suggested for several pachypleurosaurs, such as Dactylosaurus , Keichousaurus , Neusticosaurus , and Serpianosaurus from the Triassic 5 , 25 – 27 . Not all cetaceans exhibit sexual dimorphism in flipper length 28 but we did not find any case where females had longer flippers than males for a given body size.…”
Section: Sexual Dimorphism In Extant Aquatic Tetrapodssupporting
confidence: 63%
“…This led previous workers to interpret the enlargement of the limbs as a secondary sexual character of males [6]. Enlarged limbs in males probably led to improved reproductive success, as seen in salamanders with analogous dimorphism where males use their enlarged limbs during amplexus in water [17,18]. Also, enlarged limbs may have stabilized the body during courtship display in water, as in marbled newt (Triturus marmoratus) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since sexual selection promotes morphological features which allow an individual to gain reproductive success (Andersson, 1994); fecundity selection favors morphological characters which improve reproductive output (Hedrick & Temeles, 1989; Jockusch, 1997); ecological selection favors morphological characteristics which maximize survival and growth (Shine, 1989; Fontenot & Seigel Jr, 2008). Furthermore, the aquatic hynobiid salamander, L. shihi , shows male-biased SSD and limb, and female-biased head (Zhang et al, 2014), as well as all reported hynobiid salamanders shows female-biased trunk and male-biased hindlimb length (e.g., Zhang et al, 2014; Xiong et al, 2016a; Xiong et al, 2016b; Xiong et al, 2017). We hypothesize that the aquatic Pa. shangchengensis shows male-biased SSD, male-biased characters are expected in proportions of the limbs, and female-biased traits are expected in head dimensions and trunk measurements.…”
Section: Introductionmentioning
confidence: 79%
“…Family Hynobiidae is the third largest family in the Order Urodela, with two subfamilies, 10 genera, and 68 species (Frost, 2018). Studies on SD of hynobiid salamanders include species in the genera Hynobius (e.g., Kakegawa et al, 2017; Xiong et al, 2017), Liua (Zhang et al, 2014), Pseudohynobius (Xiong et al, 2016a), Salamandrella (Hasumi, 2010; Xiong et al, 2017), and Onychodactylus (Xiong et al, 2016b). Sexual size dimorphism (male-biased) has been reported in L. shihi and O. zhangyapingi ; head dimorphism (female-biased) was identified in L. shihi , O. zhangyapingi , and S. keyserlingii ; limb dimorphism (male-biased) was reported in L. shihi and H. leechii ; tail dimorphism (male-biased) was discovered in O. zhangyapingi , S. keyserlingii and H. kimurae ; and body dimorphism (represented by trunk length, female-biased) has been detected in all reported hynobiids.…”
Section: Introductionmentioning
confidence: 99%